The Moravian Beginnings of Canadian Inuit Literature. Les origines moraves de la littérature inuite au Canada. Morâviamut Pigianningit Canadamiut Inungit Allaliginniginni - Rankin, Sharon; Stenbaek, Marianne; Lindsay, Terry; Campbell, Jennifer (McGill University Library et Imaginaire Nord, 2008)
La brochure présente l'exposition sur Les origines moraves de la littérature inuite au Canada, qui porte sur les influences moraves de la littérature inuite canadienne, surtout au Labrador. The brochure presents the exhibition on The Moravian Beginnings of Canadian Inuit Literature, which deals with the influences of Moravian Canadian Inuit literature, especially in Labrador. En français, anglais et inuktitut du Labrador.